501Y.V2 and 501Y.V3 variants of SARS-CoV-2 lose binding to bamlanivimab in vitro - Haolin Liu; Pengcheng Wei; Qianqian Zhang; Zhongzhou Chen; Katja Aviszus; Walter Downing; Shelley Peterson; Lyndon Reynoso; Gregory P. Downey; Stephen K. Frankel; John Kappler; Philippa Marrack; et al. (Taylor & Francis Group, 2021)
The newly emerging variants of SARS-CoV-2 from South Africa (B.1.351/501Y.V2) and Brazil (P.1/501Y.V3) have led to a higher infection rate and reinfection of COVID-19 patients. We found that the mutations K417N, E484K, and N501Y within the receptor-binding domains (RBDs) of the virus could confer ~2-fold higher binding affinity to the human receptor, angiotensin converting enzyme 2 (ACE2), compared to the wildtype RBD. The mutated version of RBD also completely abolishes the binding of bamlanivimab, a therapeutic antibody, in vitro. Detailed analysis shows that the ~10-fold gain of binding affinity between ACE2 and Y501-RBD, which also exits in the high contagious variant B.1.1.7/501Y.V1 from the United Kingdom, is compromised by additional introduction of the K417/N/T mutation. Mutation of E484K leads to the loss of bamlanivimab binding to RBD, although this mutation does not affect the binding between RBD and ACE2.